(3NQjWI GdYdGbGJ GdJhGUdjI aj Ua GdQhVIs - (3QYO, eQjes ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2002)
(3JgOa gPg GdOQGSI Edi QUO GdYdGbGJ GdJhGUdjI YfO eLehYGJ GdCWaGd OGNd GdUa, hJJHY JZjQGJgG eMGhdI QHWgG HGdYhGed GdeSGYOI Ch GdeYjbI dbjGe CfeGW ef GdYdGbGJ GdJaGYdjI GdJj JTed CcHQ YOO eecf ef GdCWaGd ef GdfGMjJjf GdcejI hGdfhYjI, EVGaI Edi OQGSI GdYdGbGJ GdJhGUdjI aj Ua GdQhVI(B. (3Jcqhf eLJeY GdOQGSI ef (B29 (3WadG hWadI HYeQ (B4 (3SfhGJ ef Ua GdQhVI GdChdi, TGQchG H `(B28 (3fTGWkG JJQGhM eOI GdfTGW GdhGMO Hjf (B5 (3ObGFb Edi (B15 (3ObjbI, hHQabI cGejQGJ GdJUhjQ jhejG NdGd MUU GddZI GdYQHjI, ceG hGSJNOeJ JbfjI bjGS GdYdGbGJ GdGLJeGYjI Ch GdShSjheJQjI, EVGaI Edi GdedGMXGJ GdeHGTQI hGdGSJeGQGJ GdTagjI(B. (3hHYOgG JeJ eTGgOI GdCadGe GdeUhQI hJMOjO GdCfTWI GdUGdMI ddJMdjd hJaQjY cd fTGW Ydi eQGMd YOI aj LOGhd(B. (3HqjfJ GdfJGFL Cf GdCWaGd bGOQhf Ydi EbGeI YdGbGJ ef GdfeW GdJTGQcj hMJi GdJYGhfj eY JhqaQ GdTQhW GdefGSHI, ceG HqjfJ Cf GdJhRjY GdecGfj jDKQ HTcd cHjQ Ydi NQjWI GdYdGbGJ hdG HO ef PcQ JCKjQ JOqNd GdeNdeI HGdfTGWGJ Ydi Tcd hcKGaI hCeGcf JeQcR GdYdGbGJ GdJhGUdjI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Class Management; Communication; Communication; Gestion d$1 (Bune classes; Kindergarten; Maternelle; (3GOGQI GdUas; (3GdJhGUds; (3QjGV GdCWaGds